Tree of Knowledge (1997): die ontketening van kennissamehange by Willem Boshoff - Van Wyk, Josef (University of the Free State, 2018)
Since the beginning of the twentieth century there has been a growing interest in archival projects and practises as well as artists’ collections. Various artists and cultural theorists are propelled/driven by “archive fever” (Derrida 1995) and the “archival impulse” (Foster 2004). In contemporary art historical discourses there still exists a variety of discussions centred on archives, collections, archival practises and the combination thereof with artistic practises. It is within this field that the following study can be contextualised because I investigate the archival projects of Willem Boshoff. In this study I am interested in the ways in which Boshoff’s archival projects organise knowledge and how they undermine historical disciplinary divisions by combining scientific and non-scientific knowledge and portraying this in aesthetic ways (sometimes in artworks) and thereby unlocking or opening up knowledge as wisdom. The study thus serves as the first study of Boshoff’s Archive and its coherence with or relation to his artworks. The selected artworks for this study, Tree of Knowledge (1997), which consists of three artworks: Broken Garden, Druid’s Keyboard and Letters to God, have also not been interpreted before and this study serves as a first exploration. In order to enrich my interpretation of Letters to God I refer to a relatively unfamiliar religious and philosophical text written by Boshoff, Genesis (1974-1976). The study therefore also serves as the first interpretation of this text. Through my interpretation of the artworks I attempt to answer the following: In which aesthetic ways do the artworks from Boshoff’s Archive act as instruments or imaginary projections that identify, collect, exhibit, organise, connect, question or disseminate knowledge? And how do these artistic agents, instruments or fictions unravel existing orders of knowledge, thereby unleashing new clusters of knowledge? In this study the figure or image of the tree is central because all three artworks refer to the tree as a metaphor of knowledge. I approach the tree as an organisational metaphor and as a poetic fiction or device which contains various religious connotations. Thus I attempt to discover the figurative role the tree plays in these artworks. In this study I investigate the relationship between Tree of Knowledge (1997) and Boshoff’s Archive and I attempt to answer the following: how do the artworks and Boshoff’s Archive reflect aspects of each other? What are the similarities and differences in the ways in which they collect, organise, exhibit and undermine existing categories of knowledge? I approach these artworks and his Archive as explorative instruments which discover new knowledge clusters, as a result of their ability to compare, recombine, rearrange, restructure and deconstruct items from various fields of knowledge and to discover and create links between various fields. This entails a re-evaluation of and enrichment of the organisation of knowledge. I make, with caution, specific comparisons between Boshoff and artists and cultural theorists like Aby Warburg, Joseph Beuys, Walter Benjamin and Damien Hirst in order to highlight the playful, innovative and alternative ways in which they ruminate on, revisit and unfold categories of knowledge. Through these comparisons I discover a variety of associations which provide a vocabulary with which I can better define Boshoff’s project and differentiate its special niche. I also employ this vocabulary in order to highlight the coherences among various fields of knowledge, and the work of artists and cultural theorists. The comparisons also serve to situate and contextualise Boshoff and his project within art history where fictionalisation mediates knowledge. It illuminates how Boshoff’s project unravels knowledge, how it complicates the boundaries between disciplines, how his work and Archive encourage debates on interdisciplinary research and open up various interdisciplinary research possibilities.

Sedert die begin van die twintigste eeu het ‘n groeiende belangstelling in argivale projekte en kunstenaarsversamelings sy opwagting gemaak. Talle kunstenaars en vooraanstaande kultuurfigure word deur “argiefkoors” (Derrida 1995) en die “argivale impuls” (Foster 2004) gedryf. In hedendaagse kunshistoriese diskoerse bestaan daar nog steeds gesprekke rondom argiewe, versamelings, argivale praktyke en die (her-)kombinasie daarvan met kunstenaarspraktyke. Dit is in hierdie veld waarin hierdie studie geplaas kan word omdat ek Willem Boshoff se argivale projekte ondersoek. In hierdie studie is ek geïnteresseerd in die wyses waarvolgens Boshoff se argivale projekte kennis organiseer en historiese dissiplinêre vertakkings ondermyn deur wetenskaplike kennis en nie-wetenskaplike kennis te kombineer en dit op estetiese wyses (soms in kunswerke) voor te stel waardeur Boshoff wetenskaplike kennis op 'n relativerende wyse as wysheid ontsluit. Die studie dien dus as die eerste volwaardige studie van Boshoff se Argief en van hoe dit saamhang met sy kunswerke. Die gekose kunswerke vir hierdie studie, Tree of ‘n Knowledge (1997) wat bestaan uit drie werke: Broken Garden, Druid’s Keyboard en Letters to God, is ook tot dusver ongeïnterpreteer gelaat en hierdie studie dien as die eerste verkenning daarvan. Om my interpretasie van Letters to God te verryk, betrek ek ‘n relatief onbekende religieuse en filosofiese teks van Boshoff, Genesis (1974-1976). Die studie dien dus ook as die eerste interpretasie van hierdie teks. Deur my interpretasie van die werke probeer ek die volgende te beantwoord: op welke estetiese wyses ageer hierdie kunswerke uit Boshoff se Argief as instrumente of imaginêre projeksies wat kennis identifiseer, versamel, vertoon, orden, verbind, bevraagteken en dissemineer? En hoe ontrafel hierdie artistieke agente, instrumente of fiksies, bestaande kennisordes en ontketen dit daardeur nuwe kennissamehange? In hierdie studie staan die figuur of beeld van die boom sentraal omdat al drie kunswerke na die boom as kennismetafoor verwys. Ek benader soos Boshoff die boom as ‘n organiseringsmetafoor en as ‘n poëtiese versinsel wat religieuse konnotasies het en probeer daardeur die figuurlike rol wat die boom in hierdie kunswerke speel, te peil. Ek ondersoek in hierdie studie die verband tussen Tree of knowledge (1997) en Boshoff se Argief en poog om die volgende vrae te beantwoord: hoe bevrug die kunswerke en Argief aspekte van mekaar? Hoe verskil die wyses waarvolgens hulle kennis versamel, orden, vertoon en bestaande kategorieë ondermyn, of hoe kom dit ooreen? Ek benader hierdie kunswerke en sy Argief as eksploratiewe instrumente of katalisators vir die ontdekking van kennissamehange na aanleiding van hulle vermoëns om items uit verskeie velde van kennis konjektureel te vergelyk, herkombineer, herrangskik, herstruktureer, dekonstrueer en om skakels tussen verskeie velde van kennis te ontdek en daardeur die organisasie van kennis te herevalueer en te verryk. Ek tref met groot omsigtigheid produktiewe vergelykings tussen Boshoff en kunstenaars en kulturele denkers soos Aby Warburg, Joseph Beuys, Walter Benjamin en Damien Hirst na aanleiding van die speelse, innoverende en alternatiewe wyses waarmee hulle werk kennisordes herkou, hersien en ontvou. Deur hierdie vergelykings ontdek ek ‘n verskeidenheid assosiasies wat ‘n woordeskat bied om Boshoff se projek te formuleer en te onderskei van ander, en wat ek ontplooi om te dui op die samehange tussen verskeie velde van kennis, kunstenaars en kulturele denkers. Die vergelykings dien ook as die situering en kontekstualisering van Boshoff en sy projek binne die kuns- en kultuurgeskiedenis waarin fiksionalisering kennis bemiddel. Dit werp lig op Boshoff se projek, hoe hy kennis ontrafel, hoe sy projek die grense tussen dissiplines verbrokkel en kompliseer, hoe sy werk en Argief debatte rondom interdissiplinêre navorsing oopmaak en dui op verskeie verbredende interdissplinêre navorsingsmoontlikhede.
Dissertation (M.D. (Art History and Image Studies))--University of the Free State, 2018
Keywords: Aby Warburg; Archival collections; Damien Hirst; Joseph Beuys; Knowledge orders; Knowledge clusters; Organisational metaphors; Tree of Knowledge (1997); Walter Benjamin; Willem Boshoff; Willem Boshoff Archive